Lab manual for statistical analysis - McBride, Dawn M.; Cutting, J. Cooper (Los Angeles : SAGE, 2018)
"Packed with exercises, checklists, and how-to sections, this robust lab manual gives students hands-on guidance and practice for analyzing their own psychological research. The lab manual's four sections include activities that correspond directly with the chapters of Dawn M. McBride's The Process of Statistical Analysis in Psychology; activities related to data analysis projects (including data sets) that students can manipulate and analyze; activities designed to help students choose the correct test for different types of data; and exercises designed to help students write up results from analyses in APA style."--Page [4] of cover.
Preface -- Introduction for students -- Section 1. Topic activities -- Section 2. Meet the formulae -- Section 3. Data analysis projects -- Section 4. How to choose a statistical test -- Section 5. Describing and interpreting results in APA style -- Appendix: Summary of formulae -- References.
Includes bibliographical references (page 113).
Keywords: Psychology -- Statistical methods -- Laboratory manuals; Psychology -- Statistical methods; Laboratory manuals